Ku. Azhagirisami’s Anbalippu Short Stories Human Ideals - M, Murthi (International Research Journal of Tamil, 2022)
The short story has a unique place in modern prose literary forms. In this way, after the innovator of the short story, it was writer Ku. Alagirisamy who took it to another platform. He is known as the greatest personality among Tamil short story writers. Even though his works are in many forms, it can be known that he has expressed the idea that the short story form has come to convey. He has written more than a hundred short stories. Short story collections such as Anpalippu, cirikkavillai, tavappayan, varappiracatam, kaviyum katalum, cevi caykka oruvn, putiya roja, Thuruvu etc. can be mentioned here. His short story collection 'Anbalippu' won the Sahitya Academy Award in 1970. Even though he was not alive when the award was presented, the 12 short stories in this collection of his short stories are still alive. Even after 52 years, these stories are relevant and comforting to today's situation. In the short stories of K. Alagirisamy, we can know the existence of ideals suitable for human life. Research paper is the symbol of those norms. The opening short story ' Anbalippu' depicts the psychological nature of children. The stories in this collection show the ideals for human life with psychological techniques. In particular, the short stories like Anpalupu, Raja Vantirukkirar, etc. are psychological techniques and reveal human ideals. Although he was not alive when the award was given, the 12 short stories included in this collection of his short stories are still alive today. Even after 52 years, these stories are relevant to today's situation, portraying the psychological nature of children and simple language.